SISTEM INFOMASI PENGELOLAAN GAJI KARYAWAN BANK SUMSEL BABEL KANTOR CABANG PEMBANTU LEMABANG - Fahrul Rizki Pratama; Muhammad Kadafi (JURNAL FASILKOM, 2022)
Salary is a sum of money given to someone, either an employee or an employee in return for services for the business or work that has been done to the company. In determining employee payroll activities, the company should have an integrated system that can assist employee payroll activities. Bank Sumsel Babel Sub-Branch Lemabang is a branch company engaged in banking, in terms of employee payroll activities so far it is still done conventionally so that companies sometimes have difficulty in calculating employee salaries. With the problems faced at Bank Sumsel Babel Capem Lemabang, the authors raised the research with the title "Employee Payroll Information System for Bank Sumsel Babel Lemabang Sub-Branch Office".